Robin Hood the Outlaw - Dumas, Alexandre (Saga Egmont, 2022)
Continuing the story told in the classic ‘The Prince of Thieves,’ ‘Robin Hood the Outlaw’ picks up where the first book left off. Maid Marian and the Merrie Men are all present, but readers hoping that Robin has time to put down his bow and relax will be sorely disappointed. Instead, he must consider his loyalty to King Richard, while keeping one step ahead of the Sherriff of Nottingham. Throw a dastardly betrayal into the mix and you’ve got all the ingredients for a rollicking read, packed with historical detail and heroic swordplay. Alexandre Dumas (1802 – 1870) was one of the most popular French authors and playwrights of the 19th Century. After the death of his father, Dumas travelled to Paris where he eventually decided to work in the theatre. He first came to public attention at the age of 27 with his first play, ‘King Henry III and his Courts.’ After a succession of successful stage plays, Dumas turned his hand to writing novels. Many of these were serialised in newspapers, such as ‘La Comtesse de Salisbury; Édouard III,’ and ‘Le Capitaine Paul.’ Many of Dumas’ later works have been hailed as timeless classics and adapted for television and the silver screen, such as ‘The Three Musketeers’, starring ‘Lord of the Rings’´ Orlando Bloom, and ‘The Count of Monte Cristo’, starring ‘Superman’ star, Henry Cavill.